Applications of 3D printing in bioprocessing engineering - Ren, S (2023)
This thesis delves into the advancements in 3D printing technology and its application in tissue engineering and regeneration. It specifically explores the integration of 3D printing into bioprocessing engineering, covering the design and simulation of micro-fluidised bed bioreactors, the creation of composite mixers for fibrin-based emulsion scaffolds, and the use of liquefied-culture systems for cultivating scaffolds. The work highlights the unique capability of 3D printing to fabricate complex structures, addressing the constraints faced by traditional mechanical manufacturing techniques. This, in turn, markedly enhances the efficiency and efficacy of bioprocessing in tissue engineering. The thesis illustrates the role of 3D printing in bioprocessing for tissue engineering and demonstrates its technical capacities, with examples including optimising cell culture preparation, amalgamating biomaterials, and cultivating scaffolds. Firstly, 3D printing is applied into developing complex bioreactors designed for cell culture. It primarily focuses on designing, modelling, and constructing a micro-fluidised bed bioreactor as a case study to demonstrate the enhancements that additive manufacturing brings to cell growth and expansion processes. The micro-bioreactors with complex geometries are designed and fabricated with 3d printing to achieve desired fluid flow patterns to support cell culture. The bioreactor's function is analysed using a Computational Fluid Dynamics-Discrete Element Method (CFD-DEM) simulation that is experimentally validated by monitoring the movement of polycaprolactone beads through a dual-camera system, providing detailed insights into the fluidisation and internal flow dynamics. An oblate spheroid of dimensions 1.20 x 1.60 x 1.60 mm, paired with a 60° angle 2mm distributor in the bioreactor, was selected due to its favourable combination of reduced wall shear stress (lower of 0.2 pascal) and enhanced solid-liquid mass transfer (with Sherwood numbers for oxygen and glucose around 450 and 1300, respectively).The chapter concludes the superiority of the 3D printed model in facilitating rapid cell culture and managing complex flows, making it applicable in both laboratory and industrial settings. 3D printing is then applied to design and fabricate innovative mixers to manufacture fibrin-based emulsion scaffolds. It demonstrates the successful real-time mixing and integration of fibrinogen and thrombin emulsions, aiming to improve the mechanical properties and achieve optimal porosity for cell growth, especially post-freeze-drying. The section commences with a detailed analysis of three passive and three active mixers, covering their design and functionality, and then methodically evaluates their performance in terms of efficiency and shear conditions. The passive static mixer achieves an optimal balance between mixing (100%) and low shear rates (35 s^-1). However, active mixers demonstrate superior scaffold porosity at the 4 µm scale, achieving a porosity that doubles that of the passive static mixer.This advancement in mixing fibrin-based emulsions for 3D printing represents a significant stride in bio-printing. The work concludes by highlighting how this innovation broadens the horizons of bio-printing, especially by incorporating emulsion printing into mixed fluid printing techniques. The latter part of the thesis concentrates on the 3D bio-printing of complex tissue structures, and focuses on the crucial post-printing stage, where cells are embedded into scaffolds using support materials. It introduces an innovative liquefied-culture dual-functional system tailored for embedding printing methods. This system effectively dissolves support materials using a liquefaction agent blended into the nutrient solution, circulated by a pump to nourish the cell-embedded scaffold. Designed to remove support materials without damaging the scaffold or cells, the system also significantly lowers contamination risks, an essential factor in bioprinting tissues and organs. The system can remove the support material in 40 seconds at a shear rate of approximately 46 s-1. Its dual functionality not only preserves the structural and cellular integrity of the bio-printed scaffolds but also maintains the high sterility standards critical for successful tissue and organ bioprinting. The research provides valuable insights into the practical uses of 3D printing in bioprocessing engineering, potentially driving advancements and industrial applications in tissue engineering and biomanufacturing.